The Nature and Scope of the Research Journal in Enginneering and Technology Education - Kulkarni, P. D. (Journal of Engineering Education Transformations, 2009)
The author welcomes the publication of the Journal of engineering and Technology education by the NITTTR, Chandigarh. But he stresses that the beginning should be made on the basis of the sound understanding of the nature and the scope of the Journal. NITTR should explicitly define the purpose more clearly by identifying its customers and their needs for the information, pay attention to the selection of the content of the Journal, composition of the editorial board and its strategy to maintain focus on the objective of the Journal and the role NITTTR management should play to link faculty development programmes to the suit the objectives of the Journal. This paper focuses on the system of formal higher technical education.